Ethnic differences in parental attitudes and beliefs about being overweight in childhood. (March 2014) - Trigwell, J; Watson, PM; Murphy, RC; Stratton, G; Cable, NT
Objective: This study examined the relationship between ethnic background and parental views of healthy body size, concerns surrounding overweight and attitudes to perceived causes of overweight in childhood. Method: A self-report questionnaire was designed to explore parental attitudes towards childhood weight. Sampling deliberately over-represented the views of parents from minority ethnic groups. Eight-hundred-and-eight parents of school-aged children completed the questionnaire. Parental data from Asian British, Black African, Black Somali, Chinese, South Asian, White British and Yemeni groups were included in the analysis. Results: Data showed that ethnic background was significantly associated with parental beliefs that overweight children will grow out of being overweight (X 2 [12, n = 773] = 59.25, p < 0.001) and that overweight children can still be healthy (X 2 [12, n = 780] = 25.17, p < 0.05). In both cases, agreement with the statements was highest among Black Somali parents. While the majority of parents believed that both dietary behaviours and physical activity played a role in the development of overweight in childhood, Yemeni parents were more likely to attribute overweight in childhood to dietary but not physical activity causes. Conclusion: Ethnic differences in parental perceptions of weight in childhood must be considered in the design of, and recruitment to, childhood obesity interventions aimed at minority ethnic groups.